Hubungan antara Promosi Penjualan dengan Minat Beli Konsumen - Muhammad Sheva Alvieri R; Dadan Mulyana (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Geyourbe is a skincare product that emerged as a new product after many similar products had already been circulating. Sales conducted on the TikTok social media platform experienced a decline because the sales promotion carried out was insufficient to attract purchasing interest. A captivating sales promotion is needed to boost sales figures once again. Based on this phenomenon, the problems in this research can be formulated as follows: (1) the extent of the relationship between sales promotion and consumer interest in the Geyourbe skincare brand, (2) the extent of the relationship between direct discount factors and consumer interest in the Geyourbe skincare brand, (3) the extent of the relationship between bundling package factors and consumer interest in the Geyourbe skincare brand. The researcher used correlational analysis technique with a quantitative approach. The population of this study is consumers of the product who follow the TikTok account @Geyourbeofficial, totaling 21,300 followers. By using the non-probability sampling technique, this research obtained a sample of 100 respondents. The data collection technique used in the research is a questionnaire. The data analysis techniques used in this research are descriptive analysis technique and inferential analysis technique. The results of this research are as follows: there is a positive and significant relationship between sales promotion and consumer interest in the Geyourbe Skincare brand, which falls into the strong/high category. Abstrak. Geyourbe merupakan produk skincare yang merupakan produk baru setelah banyaknya jenis produk yang serupa beredar lebih dulu. Penjualan yang dilakukan di media sosial TikTok mengalami penurunan karena promosi penjualan yang dilakukan kurang dapat menarik minat beli. Dibutuhkan promosi penjualan yang menarik demi menaikan angka penjualan kembali. Berdasarkan fenomena tersebut, permasalahan dalam penelitian ini dapat dirumuskan sebagai berikut: (1) seberapa besar hubungan antara promosi penjualan dengan minat beli konsumen pada merek skincare Geyourbe? (2) seberapa besar hubungan antara faktor potongan harga langsung dengan minat beli konsumen pada merek skincare Geyourbe? (3) Seberapa besar hubungan antara faktor paket Bundling dengan minat beli konsumen pada merek skincare Geyourbe?. Peneliti menggunakan Teknik analisis korelasional dengan pendekatan kuantitatif. Populasi dari penelitian ini merupakan konsumen produk yang mengikuti akun TikTok @Geyourbeofficial yang berjumlah 21.300 pengikut. Dengan menggunakan Teknik pengambilan sampel penelitian ini yaitu non- probability sampling diperoleh sampel penelitian sebanyak 100 responden. Teknik pengumpulan data yang digunakan dalam penelitian adalah kuesioner. Adapun Teknik analisis data yang digunakan pada penelitian ini yaitu Teknik analisis deskriptif dan Teknik analisis inferensial. Hasil dari penelitian ini adalah: terdapat hubungan yang positif dan signifikan antara promosi penjualan dengan minat beli konsumen pada merek Skincare Geyourbe yang termasuk kedalam kategori kuat/tinggi.